Present Status of Elliptio Complanatus in Douglas Lake, Michigan - Jerry C. Smrchek (Hello World!, 1971)
Matteson (1948) in studying the species' life his ory in the mid 1940's, transported mussels from Ocqueoc River and Ocqueoc Lake to Douglas Lake and placed them in shallow water near shore to serve as a storage population and stock for experimentation. He states that some clams stored over the winter moved into deeper water with the return of warmer weather and became scattered and difficult to retrieve.